Interactions between the Re-Emerging Pathogen Corynebacterium diphtheriae and Host Cells - Ott, Lisa; Möller, Jens; Burkovski, Andreas (International Journal of Molecular Sciences, 2022)
Corynebacterium diphtheriae, the etiological agent of diphtheria, is a re-emerging pathogen, responsible for several thousand deaths per year. In addition to diphtheria, systemic infections, often by non-toxigenic strains, are increasingly observed. This indicates that besides the well-studied and highly potent diphtheria toxin, various other virulence factors may influence the progression of the infection. This review focuses on the known components of C. diphtheriae responsible for adhesion, invasion, inflammation, and cell death, as well as on the cellular signaling pathways activated upon infection.
CRIS-Team Scopus Importer:2022-04-08
Keywords: Apoptosis; Diphtheria; Diphtheria toxin; Mycolic acids; Necrosis; Pyroptosis; Shiga-like toxin